The Influence of Risk Perception and Demographic Factors on Investment Decisions Mediated by Investment Motivation Among Millennial Generation Students - Mustari Mustari; Andi Pallawagau; Nur Arisah (Cita konsultindo, 2024)
This research was conducted with the aim of knowing the effect of risk perception, demographic factors on investment decisions by students as millennials through investment motivation as a mediating variable. Collecting data using a questionnaire distributed online. The type of research used in this research is descriptive quantitative research with a population of 30 respondents as millennial generation students. The data analysis technique used is path analysis. The results of this study indicate that: (1) risk perception has a positive and significant direct effect on investment decisions; (2) demographic factors have no direct or indirect positive and significant effect on investment decisions; (3) investment motivation has a positive and significant direct effect on investment decisions; (4) investment motivation is able to mediate the effect of risk perception on investment decisions; (5) investment motivation is able to mediate the influence of demographic factors on investment decisions.